2017
DOI: 10.1093/ehjci/jex243
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular magnetic resonance imaging in patients with cardiac implantable electronic devices: a device-dependent imaging strategy for improved image quality

Abstract: Device type and location constitute the main independent predictors of CMR image quality and thus, need to be considered during protocol adaptation. Most notably, post-contrast SGE cine imaging proved superior to conventionally used SSFP sequences. Thus, following the proposed device-dependent CMR imaging strategy, diagnostic image quality can be achieved in the majority of device patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 11 publications
6
26
0
Order By: Relevance
“…Consecutive patients referred for CMR imaging with an ICD between June 2015 and December 2018 formed the study population. The CMR examination rigorously followed a previously published, standardized protocol [5]. All patients underwent chest x-ray prior to the CMR examination and in the presence of abandoned, epicardial or fractured leads, CMR imaging was not performed (i.e.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consecutive patients referred for CMR imaging with an ICD between June 2015 and December 2018 formed the study population. The CMR examination rigorously followed a previously published, standardized protocol [5]. All patients underwent chest x-ray prior to the CMR examination and in the presence of abandoned, epicardial or fractured leads, CMR imaging was not performed (i.e.…”
Section: Patient Populationmentioning
confidence: 99%
“…However, more recent research addressed the pivotal issue of achieving adequately high diagnostic image quality of cardiovascular magnetic resonance (CMR) imaging in patients with implanted cardioverter defibrillator (ICD) and utilized well-established spoiled-gradient echo cine sequences following gadolinium-containing contrast agent application in combination with wideband late-gadolinium enhancement (LGE) imaging. Thus, the fundamental diagnostic CMR modules of basic ventricular functional assessment and myocardial tissue characterization have eventually become available for routine clinical usage in ICD patients either [5][6][7][8]. While previous investigations have largely focused on safety and image quality, the clinical impact and usefulness of CMR imaging in ICD patients have not been evaluated yet.…”
Section: Introductionmentioning
confidence: 99%
“…Strategies to reduce artifact generally yield interpretable results and so ensure clinical yield is high, which is particularly important for patients with ICDs [33]. These strategies include using spoiled gradient echo cines, shorter echo times, or wideband inversion recovery pulses for late gadolinium enhancement [34,35].…”
Section: Mri Artifactmentioning
confidence: 99%
“…Scanning techniques are developing at a rapid rate; notably the recent study by Hilbert et al [44] has confirmed the utility of alternative protocols to help produce diagnostic grade images.…”
Section: Image Quality Optimisationmentioning
confidence: 99%